Two new species of Amphinemura (Plecoptera: Nemouridae) from Taiwan Province on the southeast coast of China - Zhao, Meng-Yuan; Du, Yu-Zhou (Zootaxa, 2021)
Two new species of Amphinemura were described and illustrated from Taiwan Province of China: Amphinemura reni Du & Zhao, sp. nov. and Amphinemura triquetra Zhao & Du, sp. nov. The morphological characteristics of the new species were compared to related taxa. Additionally, a key to the adult males of Amphinemura known from Taiwan Province of China was given in this paper.